Dinamika Kelompok Dalam Cooperative Learning Model: Analisis Psikologi Sosial terhadap Interaksi Siswa dalam Pembelajaran Pendidikan Agama Islam - Rofiqi, Rofiqi; Kurnia Nofita Rahmawati, Roro (Al-Riwayah : Jurnal Kependidikan, 2023)
The cooperative learning model aims to stimulate the growth of student competence from social psychological aspects. The dynamics that emerge in groups allow students to interact optimally in a broader context. The purpose of this article is to explore group dynamics in the cooperative learning model seen from the aspect of student interaction in Islamic Religious Education lessons. The method used is library research in which the process of searching for meaning is generated from various literary sources to produce descriptive data in the form of text and words. The results of this research indicate that in the cooperative learning model, group dynamics are very important to achieve effective learning goals. This also applies in the context of Islamic Religious Education lessons. Group dynamics in cooperative learning include aspects of student interactions, their roles in the group, and the way they collaborate. Several important aspects of group dynamics in Islamic Religious Education learning include; division of roles, discussion, collaboration, inclusive approach, shared responsibility, peer evaluation, facilitator or teacher.